The history of Israel - Blumberg, Arnold, 1925-2006 (Greenwood histories of the modern nations., 1998)
Traces the history of Israel, detailing such events as the beginnings of Zionism, the two decades of growth, the 1967 Six Day War and the six-year aftermath, the Likud revolution of 1977-83, and the peace process of 1992-96.